Evaluation of a Recycling Strategy for Polymer-Bonded Magnets Based on Thermosets - Rösel, Uta; Drummer, Dietmar (Recycling, 2024)
Polymer-bonded magnets are increasingly being used in terms of applications in drive technology and, more specifically, in new concepts based on reluctance motors. The increasing demand for polymer-bonded magnets, especially in the context of electromobility, is leading to a shortage of materials, mainly in terms of the finite resource neodymium–iron–boron (NdFeB). So far, the recycling strategy for polymer-bonded magnets based on thermosets is pyrolysis, which leads to either a massive reduction of the magnetic properties or a high energy requirement. Therefore, the paper investigates an alternative recycling strategy for polymer-bonded magnets based on thermosets based on the reusage of shreds. Several influencing factors such as the form of the carrier material and the temperature level were varied in order to find a suitable recycling method. It was found that the magnetic properties were reduced by at least 15% compared to the pure material. The required energy and the CO2 emission were reduced by 90% compared to the pyrolysis. Thus, the strategy of recycling polymer-bonded magnets based on thermosets by the reusage of shreds leads to improved conditions compared to pyrolysis and is, therefore, a suitable alternative.<br
Keywords: hard magnetic filler; recycling strategy; thermoset; mechanical reusage of shreds